Pelatihan pemanfaatan AI untuk personal branding siswa SMA Ibnu Sina Malang - Ariska, Ricky Angga; Yuliarini, Sarah; Purwitasari, Fadilla (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
In the rapidly evolving digital age, learning artificial intelligence (AI) is essential. Many AI technologies have already been developed to support operational activities across fields such as education, design, and business. However, the importance of learning AI extends beyond its use in daily activities. AI offers benefits such as opening up exciting career opportunities, sparking inspiration and innovation in creative fields, and more. High school students can use AI to prepare for their schooling and post-graduation activities. Therefore, high school students should be guided to optimize AI to build their personal branding, thereby providing added value to high school graduates. The community service activity was held at Ibnu Sina High School in Malang, with 12th-grade students as the audience. The method used is training and practice. Students were taught to use and maximize the AI features available in Canva and Gamma. Only a few students were already using these applications but had not yet fully utilized their features. The expected outcome of this training is to equip students with digital and AI skills that can be applied as students, employees, or entrepreneurs.